PHYSICAL AND CHEMICAL PROPERTIES OF GROUNDWATER IN BANJARARUM AREA AND ITS VICINITY, WEST PROGO - Peni, Sri Ning; R. A., T. Listyani (Institut Teknologi Nasional Yogyakarta, 2019)
Groundwater in the Banjararum area is found in various rocks that build the West Progo Hills, including the Nanggulan and the Andesite Breccia Formations. Groundwater can be found in dug wells and springs. Field surveys show that the groundwater is generally clear, tasteless and odorless, except for the well at Ngipikrejo. Chemical test results from four samples showed that groundwater in limestone has Ca, Mg - HCO3 type, whereas in volcanic rocks of type Ca - HCO3 and Ca, Na - HCO3. Groundwater chemistry type is generated from the soil, mineral dissolution in sedimentary rocks and igneous rocks as well as the atmosphere through rainwater. The considerable content of NO3 in the Ngipikrejo area indicates pollution from human activities, plants or animal dung. In general, groundwater in the study area is suitable for use as clean water or drinking water, characterized by a measurable pH in the field of 6.6 - 7.2 and TDS 54 - 155 ppm. Nevertheless, laboratory test results show that groundwater samples are water-filled, with a hardness of 135,866 - 778,048 (moderately hard - very hard), so special treatment is required before drinking.